When to start ART in adults? The results of HPTN 052 move us closer to a test-and-treat policy - Nathan Geffen (AOSIS, 2011)
When is the best time to initiate antiretroviral therapy (ART) in adults? This is a vital question in HIV treatment and prevention services. More specifically, is the 350 cells/µl CD4 count threshold recommended by current World Health Organization (WHO) guidelines sufficient, or should we move to a 'test-and-treat' approach in which anyone who tests HIV-positive is offered ART, irrespective of their CD4 count? The recently announced results of the HPTN 052 trial take us closer, but not all the way, to a test-and-treat approach.